PENYESUAIAN DIRI MAHASISWA NTT DI UNIVERSITAS WIJAYA PUTRA SURABAYA - Anugrahani, Dinda Alfika; Nurlaily, Lutfiana; Rahmadian, Muhammad Reza; Grahani, Firsty Oktaria; Agustin, Ardianti (Pusat Studi GESI - UWP, 2025)
Abstract This research examines the adaptation of students from East Nusa Tenggara (NTT) studying at Wijaya Putra University Surabaya, Java Island.The main focus is on how students face the challenges of adapting to new cultures, languages, and habits in a different educational environment.This research uses a qualitative approach with a phenomenological method to understand how NTT students adapt at Wijaya Putra University Surabaya.The subjects of the study are 2 students aged 22 years who are in their 3rd and 5th semesters.Through interviews with students from out of town, it was found that they experienced culture shock, language difficulties, and social pressure, but gradually managed to adapt with social support and interaction.Effective adaptation contributes to academic success and mental well-being.These findings are important as a basis for developing mentoring programs that support cultural and language adaptation for students from afar. Abstrak Penelitian ini mengkaji penyesuaian diri mahasiswa perantau asal Nusa Tenggara Timur (NTT) di Universitas Wijaya Putra Surabaya, Pulau Jawa. Fokus utama adalah bagaimana mahasiswa menghadapi tantangan adaptasi budaya, bahasa, dan kebiasaan baru di lingkungan pendidikan yang berbeda. Penelitian ini menggunakan pendekatan kualitatif dengan metode fenomenologi untuk memahami bagaimana penyesuaian diri mahasiswa rantau NTT di Universitas Wijaya Putra Surabaya. Subjek penelitian adalah 2 mahasiswa yang berusia 22 tahun dan menginjak semester 3 dan 5. Melalui wawancara dengan mahasiswa rantau, ditemukan bahwa mereka mengalami culture shock, kesulitan bahasa, dan tekanan sosial, namun secara bertahap mampu menyesuaikan diri dengan dukungan sosial dan interaksi. Penyesuaian diri yang efektif berkontribusi pada keberhasilan akademik dan kesejahteraan mental. Temuan ini penting sebagai dasar pengembangan program pendampingan yang mendukung adaptasi budaya dan bahasa bagi mahasiswa rantau.